Antifungal antibiotic of the Basidiomycete Oudemansiella mucida. III. Nuclei in the hyphae of mono- and dikaryons - Semerdzieva, M; Musílek, V (Folia microbiologica, 1977)
Nuclear ratios were studied in terminal and subterminal cells of various mycelia of the basidiomycete Oudemansiella mucida, the producer of the antifungal antibiotic mucidin (MuciderminR Spofa). The dikaryon, the monokaryon, and the mucidin-producing strain that had been cultivated for a long time under submerged conditions were compared. Dedikaryotization was found to have taken place in the producing strain. The originally dikaryotic culture with characteristic clamp connections on the mycelium and with two nuclei in every hyphal cell lost permanently the clamp connections, probably owing to continuous intense agitation. The hyphae contained solely mononuclear cells. Mating with a compatible monokaryon yielded a dikaryon capable of normal fructification.
Keywords: kultivační média; Bacteriological Techniques; buněčné jádro; Basidiomycota; Antifungal Agents; Cell Nucleus; antifungální látky; bakteriologické techniky; Culture Media